1991
DOI: 10.21273/jashs.116.1.47
|View full text |Cite
|
Sign up to set email alerts
|

Lowbush Blueberry Quality Changes in Response to Mechanical Damage and Storage Temperature

Abstract: Postharvest response of wild lowbush blueberry (Vaccinium angustifolium Ait. and V. myrtilloides Michx.) to mechanical damage and storage temperature was studied during 2 years. Fruit weight loss and the incidence of shriveled or split berries were major components that contributed to the loss of marketable yield resulting from mechanical damage and storage temperature. Decay of berries resulted in only 1% to 2% of the total marketable fruit loss. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
25
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 8 publications
3
25
0
Order By: Relevance
“…Damaged berries: The method of Sanford et al (1991) was used. A 50 g sample (approximately 150-190 berries) was removed from each of the 18 treatments.…”
Section: Measurement Of Quality After Frozen Storagementioning
confidence: 99%
“…Damaged berries: The method of Sanford et al (1991) was used. A 50 g sample (approximately 150-190 berries) was removed from each of the 18 treatments.…”
Section: Measurement Of Quality After Frozen Storagementioning
confidence: 99%
“…Sanford et al (1991) showed that mechanical damage of lowbush blueberries (V. angustifolium) may decrease firmness by 15.3 to 32.1%. Recently, research with MH and HH rabbiteye blueberries has suggested that mechanical damage during harvesting and grading accounts for a major portion of the firmness loss of fruit, and immediate cooling following harvest has only a slight influence on firmness retention (NeSmith et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…After this period, no significant differences ( P > 0.05) were observed between the WL of coated and control blueberries. WL of between approximately 6.7% (control) and 11% (CB) was observed after 13 days at 5 °C; Sanford et al reported 7.6% weight loss when blueberries were stored for 14 days at 5 °C. The decrease in moisture content is related to WL and to loss of firmness since blueberries are harvested fully ripe …”
Section: Resultsmentioning
confidence: 99%